The Parasites of Cats in Türkiye - Öykü Barılı; Tuğçe Tuygun; Elif Burcu Gençay Topçu; Şinasi Umur (Türkiye Parazitoloji Dergisi, 2023)

(untitled)
Cats have an important and different place due to their close relationships with humans. Since most of the parasites they carry are zoonotic, it is important to detect them. According to the research, Dipylidium caninum, Joyeuxiella pasqualei, Toxocara spp., Toxascaris leonina, Giardia spp., Isospora spp., and Toxoplasma sp. were found to be higher in cats compared to other parasites. It has been determined that scabies and flea infestations are common as ectoparasites. This review aims to present the reported parasites and their prevalence rates in cats in Türkiye.